STRATEGIC SCHOOL FINANCIAL MANAGEMENT AND ITS IMPACT ON EDUCATIONAL QUALITY: A PARTICIPATORY, TRANSPARENT, AND ACCOUNTABLE APPROACH - Khalimatu Sa’diyah; Tondy Natama Pulungan; Deny Hadi Siswanto; Siti Atwano Pisriwati (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the financial management mechanisms at SMA Muhammadiyah Mlati in improving educational quality. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentary studies. The results show that financial planning is carried out systematically and participatively through the development of the School Activity and Budget Plan (RKAS), involving various school stakeholders. Financial implementation upholds the principles of transparency and accountability through a tiered verification system and orderly documentation. Furthermore, supervision is conducted sustainably through internal monitoring by the principal and external oversight by the foundation. Budget utilization is strategically focused on increasing teacher competence, providing technological facilities, and student character-building programs. Therefore, the integration of democratic planning and strict supervision creates effective fund utilization that directly impacts the quality of graduates. This study recommends the need for integrated digitalization of financial administration to accelerate real-time reporting and the strengthening of external partnerships to diversify funding sources to support sustainable educational innovation in the future.